A “five rights separation” framework for data rights confirmation in data element circulation - Jianbo Zhao; Huailiang Liu; Shanzhuang Zhang; Kai Shu; Qisen Fang; Weili Zhang; Chufan Tan; Xiaojin Zhang; Yuehai Wang; Yanwei Qi (Humanities & Social Sciences Communications, 2025)
Abstract Clarifying the rights subjects and their corresponding rights in data element circulation, and constructing a rational data rights confirmation framework,are crucial prerequisites for ensuring the smooth circulation of data elements. Employing an improved evidence-based model, this paper conducts evidence-based research on the traditional methodologies of data rights confirmation in the three major economic entities: the European Union, the United States, and China. The findings indicate that the European Union demonstrates strong systematicity and innovativeness in data rights confirmation, the United States exhibits strong specificity and adaptability, and China shows strong collectivism and developmental characteristics. As a result, this paper proposes a “five rights separation” framework for ternary data subjects, which balances the interests and needs of different data subjects while ensuring both efficiency and security in data element circulation. For the first time, this paper provides a new construction method and theoretical framework for data rights confirmation in data element circulation.Future research can expand the scope and depth of evidence-based studies, conduct empirical research, and implement pilot projects.